Determinant Factors of Stress in Family Caregiver in the Care of Older adults with Chronic Disease: Literature Review - Widiastuti, Ni Kadek Nefi; Kamaryati, Ni Putu; Rismawan, Made; Sriasih, Ni Kadek (Babali Publisher, 2025)
Introduction: Chronic diseases are degenerative conditions that require long-term treatment. Older adults patients who are unable to care for themselves independently often rely on assistance from others, particularly family members, who serve as family caregivers. Stress among family caregivers is a significant issue encountered when caring for older adults individuals with chronic diseases. This research aims to analyze the factors contributing to stress in family caregivers providing care for older adults people with chronic diseases. Methods: This study employed a literature review design, analyzing 16 articles published between 2017 and 2024 in either Indonesian or English. Articles included were complete and relevant to the study objectives. The PRISMA checklist was utilized to guide the protocol and evaluation process, ensuring the appropriate selection of studies aligned with the literature review objectives. Results: Several factors contribute to stress among family caregivers caring for older adults individuals with chronic diseases, including (1) age of family caregiver; (2) sex; (3) Llow levels of education and knowledge can trigger stress family caregiver; (4) type of work and income level; and (5) the length of treatment carried out family caregiver also affects the stress he experiences Conclusion: Nurses can play a vital role in supporting family caregivers by conducting comprehensive assessments, providing individualized support, teaching stress management techniques, offering caregiver education, and facilitating respite care.